1987
DOI: 10.1037/0278-7393.13.4.640
|View full text |Cite
|
Sign up to set email alerts
|

Sexing day-old chicks: A case study and expert systems analysis of a difficult perceptual-learning task.

Abstract: The sexing of day-old chicks has been regarded as an extraordinarily difficult perceptual task requiring years of extensive practice for its mastery. Experts can sex chicks at over 98% accuracy at a rate of 1,000 chicks per hour spending less than a half second viewing the cloacal region. Naive subjects were shown 18 pictures of cloacal regions of male and female chicks (in random appearing arrangement) and asked to judge the sex of each chick. The pictures included a number of rare and difficult configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
193
1
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(200 citation statements)
references
References 11 publications
4
193
1
2
Order By: Relevance
“…For example, Mayer and Gallini (1990) showed that problem solving involving mechanical devices (e.g., car brakes) was facilitated when a previously shown explanation of those devices was accompanied by a diagram of the component parts and their functions. Likewise, Biederman and Shiffrar (1987) showed that novices, after minimal instruction with a few simple diagrams, could match the performance of highly skilled experts on a perceptual learning task. The task involved the sexing of day-old chicks, a commercially relevant skill that had previously defied pictorial representation or training and that previously could only be learned through extensive practice (up to 1,000,000 trials).…”
Section: Schematic Diagrams and The Acquisition Of Complex Knowledgementioning
confidence: 99%
“…For example, Mayer and Gallini (1990) showed that problem solving involving mechanical devices (e.g., car brakes) was facilitated when a previously shown explanation of those devices was accompanied by a diagram of the component parts and their functions. Likewise, Biederman and Shiffrar (1987) showed that novices, after minimal instruction with a few simple diagrams, could match the performance of highly skilled experts on a perceptual learning task. The task involved the sexing of day-old chicks, a commercially relevant skill that had previously defied pictorial representation or training and that previously could only be learned through extensive practice (up to 1,000,000 trials).…”
Section: Schematic Diagrams and The Acquisition Of Complex Knowledgementioning
confidence: 99%
“…In that case the expert can direct focal attention to the critical locations, allowing the independent visual process to do the rest. The most remarkable case of such expertise was investigated by Biederman and Shiffrar (1987) and involves expert "chicken sexers." Determining the sex of day-old chicks is both economically important and also apparently very difficult.…”
Section: The Case Of Expert Perceiversmentioning
confidence: 99%
“…However, we would like to finish on another point related to the performance of expert perceivers. Pylyshyn considers the case of chick sexing (Biederman & Shiffrar 1987) and argues that instruction teaches the sexer how "to bring the independent visual system to bear at the right spatial location" (sect. 6.2, para.…”
Section: Expert Perceivers and Perceptual Learningmentioning
confidence: 99%
See 2 more Smart Citations